ACTION RESEARCH CAPABILITY OF MATHEMATICS TEACHERS - Jeannette M. Geva; Aldin D. Labo, MAEd (European Journal of Humanities and Educational Advancements, 2023)
With the issuance of DepEd Order No. 16, s. 2017, basic education teachers in the Philippines are encouraged to conduct action researches towards the promotion of evidence-based decision-making in instruction and administration. Considering this directive, the researchers primarily intended to assess the action research capabilities of the mathematics teachers in secondary schools in Bulan Districts in Sorsogon. Specifically, this study aimed to (1) identify the profile of the mathematics teachers, (2) determine the action research capabilities of the teachers along seven variables; and (3) propose interventions based on the results of the study. The respondents of this research were a total enumeration 63 permanent teachers who were handling mathematics subjects in junior and senior high schools in the four Districts of Bulan, Sorsogon in the school year 2021-2022. The primary research instrument is a survey-questionnaire which was designed based on the Teacher’s Competency in Action Research (TCAR) Scale. Findings revealed that most of the mathematics teachers are female, aged 35 years and below, single, have baccalaureate degree, with Teacher I position, have been in service for 1-10 years, have attended 1-3 trainings on action research, and have no other designations. Furthermore, the mathematics teachers are moderately capable in terms of selecting topic for professional growth, planning an action research project, integrating technology in analyzing data, analyzing and presenting action research data, and reflecting on and communicating results. They are capable in terms of integrating technology in writing literature and integrating ethics in action research. The researcher recommends a comprehensive training for teachers on action research covering the seven variables identified, including the use of computer software